DIVERSITY INDICES OF ZOOPLANKTON IN LAKE ALAU, NORTH-EAST ARID ZONE OF NIGERIA - USMAN, A.; SOLOMON, S.G; OKAYI, R.G. (Nigerian Journal of Fisheries, 2014)
Zooplankton species of Lake Alau were investigated in five stations, designated as station A, B, C, D and E (SA, SB, SC SD, SE). The sampling was done in the morning before 8:00 am, on monthly basis for a period of ten months (July 2012 to April 2013) covering both wet and dry seasons and analysed. Pour-through method was used to collect the samples. The results show that the monthly trend of Shannon-Weiner index for the Lake decreased as follows: January > November > December > February > October > March > April > July > August > September. The maximum (2.119) values of zooplankton species diversity was recorded in January whereas the minimum (1.911) was observed in September. The concentration of dominance was in the order September > August > July > April > October > March > February > December > November > January. The species richness index ranged from 1.564 (April) to 1.414 (July). The equitability or evenness index was highest in January (0.920) and least (0.830) in September. Species heterogeneity was in the order January > November > December > February > March > October > July=April > August > September. The trend of Shannon-Weiner index for stations in Lake Alau was depicted as SA>SB>SD>SC>SE. The minimum value (2.021) of zooplankton species diversity was recorded in SA where as the minimum (1.875) was observed for SE. In conclusion, Lake Alau is fairly rich in terms of zooplankton abundance and diversity. More intensive study of the zooplankton species in Nigerian lakes will lead to the documentation of other species and wider distribution of many others than those that were recorded in the current study. This will lead to greater understanding of the factor that controls the distribution of these species.